A Self‐Powered Dielectrophoretic Microparticle Manipulation Platform Based on a Triboelectric Nanogenerator. Issue 1 (18th November 2022) - Zhou, Jian; Tao, Ye; Xue, Rui; Ren, Yukun
Abstract: Lab‐on‐a‐chip systems aim to integrate laboratory operations on a miniaturized device with broad application prospects in the field of point‐of‐care testing. However, bulky peripheral power resources, such as high‐voltage supplies, function generators, and amplifiers, hamper the commercialization of the system. In this work, a portable, self‐powered microparticle manipulation platform based on triboelectrically driven dielectrophoresis (DEP) is reported. A rotary freestanding triboelectric nanogenerator (RF‐TENG) and rectifier/filter circuit supply a high‐voltage direct‐current signal to form a non‐uniform electric field within the microchannel, realizing controllable actuation of the microparticles through DEP. The operating mechanism of this platform and the control performance of the moving particles are systematically studied and analyzed. Randomly distributed particles converge in a row after passing through the serpentine channel and various particles are separated owing to the different DEP forces. Ultimately, the high‐efficiency separation of live and dead yeast cells is achieved using this platform. RF‐TENG as the power source for lab‐on‐a‐chip exhibits better safety and portability than traditional high‐voltage power sources. This study presents a promising solution for the commercialization of lab‐on‐a‐chip. Abstract : A self‐powered DEP microparticle manipulation platform based on a triboelectric nanogenerator (TENG) is proposed, which performs high‐efficiency cell separation. This work provides an ideal scheme for improving the portability of microfluidic chips and is beneficial to the commercialization of lab‐on‐a‐chip systems.